La motricidad fina y su importancia en el aprendizaje de la pre-escritura de los niños y niñas del primer año de educación básica del instituto educativo Antonio Peña Celi, de la ciudad de Loja, periodo 2014-2015. - Novillo Tacuri, María Belén (2016)
This final Project wich name is LA MOTRICIDAD FINA Y SU IMPORTANCIA EN EL APRENDIZAJE DE LA PRE-ESCRITURA DE LOS NIÑOS Y NIÑAS DEL PRIMER AÑO DE EDUCACIÓN BÁSICA DEL INSTITUTO EDUCATIVO ANTONIO PEÑA CELI, DE LA CIUDAD DE LOJA, PERIODO 2014-2015. It is a research work whose General Objective is: To know the importance of fine motor learning pre-writing children of the first year of basic education Educational Institute Antonio Peña Celi city of Loja, period 2014 -2015. The methods used for the preparation of this research work were: Scientific, inductive-deductive, Descriptive; the techniques used were: The survey of Parents of First Year Basic Education to know the importance of learning fine motor pre-writing, interview aimed at teaching the first year of basic education, and applied observation guide children to determine the degree of difficulty presented in learning prewriting. About the results, 100% of parents surveyed said they believe the fine motor skills is important in learning prewriting. According to the results of the observation guide it has concluded that 80% of children in the first year of basic education written correctly and make proper use of the pencil so it is very satisfying.